2018
DOI: 10.1021/acscatal.8b00797
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Loading-Dependent Reaction Barriers over Mixed RuO2/TiO2 Catalysts

Abstract: Mixed-metal oxides are one of the most frequently used catalysts in chemical industry, because the superior catalytic reactivity can be achieved by taking advantage of the synergetic effects of their parent oxides. However, the interfacial electronic interactions between metal oxides remain unclear, because of their structural complexity. This paper describes the modulation of catalytic performance of mixed RuO 2 /TiO 2 catalysts via adjusting the loading amount of RuO 2 . We show that, at very low loadings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 53 publications
3
25
0
Order By: Relevance
“…Studies on Ru/a-TiO 2 with different Ru loadings suggest that the effect of hydrogen spillover and charge transfer is general. Consistent with the catalytic performance (selectivity to CH 4 ), the hydrogen spillover and electron transfer, detected by operando DRIFT spectra (Figure 4c), NAP-XPS analysis (Table 1a nd Figure S15) and in situ PL measurements ( Figure S14c), decreased greatly on 5Ru/a-TiO 2 .T he weaker spillover should be related to adecrease in exposed a-TiO 2 surface Os ites with Ru loading increase, [44] which lowers the possibility of forming Ti-O(H)-Tibyhydrogen spillover.Furthermore,the study combining synchrotronradiation photoelectron spectroscopy,s canning tunneling microscopy and density functional calculations indicated that the charge transfer across metal/support interface was associated with metal particle size. [45] Ther elatively larger particles may limit the charge transfer as well.…”
Section: Methodssupporting
confidence: 68%
“…Studies on Ru/a-TiO 2 with different Ru loadings suggest that the effect of hydrogen spillover and charge transfer is general. Consistent with the catalytic performance (selectivity to CH 4 ), the hydrogen spillover and electron transfer, detected by operando DRIFT spectra (Figure 4c), NAP-XPS analysis (Table 1a nd Figure S15) and in situ PL measurements ( Figure S14c), decreased greatly on 5Ru/a-TiO 2 .T he weaker spillover should be related to adecrease in exposed a-TiO 2 surface Os ites with Ru loading increase, [44] which lowers the possibility of forming Ti-O(H)-Tibyhydrogen spillover.Furthermore,the study combining synchrotronradiation photoelectron spectroscopy,s canning tunneling microscopy and density functional calculations indicated that the charge transfer across metal/support interface was associated with metal particle size. [45] Ther elatively larger particles may limit the charge transfer as well.…”
Section: Methodssupporting
confidence: 68%
“…TheBET surface areas of TiO 2 supports are about 21 m 2 ,t herefore the Vd ensity of 1V/TiO 2 was determined to be 0.89 mmol Vp er 100 m 2 of titanium oxide (namely,0 .081 wt %v anadium oxide per m 2 of titanium oxide), which is close to the previous reported theoretical monolayer (a value of 0.1 wt %v anadium oxide per m 2 of titanium oxide surface area). [17] So we suggest that the VO x with 1wt% Vl oadings completely encapsulate the TiO 2 substrate and reach to the monolayer dispersion capacity. TEM and HRTEM images showed that the particle size of TiO 2 supports is about 50 nm with ad -spacing of 0.325 nm, which is ascribed to TiO 2 (110) (Supporting Information, Figure S1C,D).…”
Section: Resultsmentioning
confidence: 76%
“…Previously, extensive studies showed that metal nanoparticles and single atom catalysts exhibit variable catalytic reactivity when they are deposited on different supports, such as SiO 2 , Al 2 O 3 , CeO 2 , TiO 2 , FeO x and many others. [6][7][8][9][10][11][12] Surprisingly, the inuence of different surface states of oxide supports on the structure and catalytic performance of metal catalysts has only been studied using model surface science systems while little is known about this factor in real supported catalysts. [13][14][15][16] Recently, several related studies on this issue have been published.…”
Section: Introductionmentioning
confidence: 99%